2013
DOI: 10.4049/jimmunol.1202525
|View full text |Cite
|
Sign up to set email alerts
|

Dynein Light Chain LC8 Inhibits Osteoclast Differentiation and Prevents Bone Loss in Mice

Abstract: NF-κB is one of the key transcription factors activated by receptor activator of NF-κB ligand (RANKL) during osteoclast differentiation. The 8-kDa dynein L chain (LC8) was previously identified as a novel NF-κB regulator. However, its physiological role as an NF-κB inhibitor remains elusive. In this study, we showed the inhibitory role of LC8 in RANKL-induced osteoclastogenesis and signaling pathways and its protective role in osteolytic animal models. LC8 suppressed RANKL-induced osteoclast differentiation, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 52 publications
0
21
0
Order By: Relevance
“…Ovariectomy (OVX) and microcomputed tomography were carried out as previously described in Kim et al (35). Eight-week-old C57BL/6 female mice were randomly divided into the following groups (n = 5 in each group): sham-treatment, OVX, and OVX followed by DL treatment.…”
Section: Ovariectomy and Microcomputed Tomography Imagingmentioning
confidence: 99%
“…Ovariectomy (OVX) and microcomputed tomography were carried out as previously described in Kim et al (35). Eight-week-old C57BL/6 female mice were randomly divided into the following groups (n = 5 in each group): sham-treatment, OVX, and OVX followed by DL treatment.…”
Section: Ovariectomy and Microcomputed Tomography Imagingmentioning
confidence: 99%
“…Additionally, in vivo studies of LC8-IDP duplexes are complicated by the ubiquitous nature of LC8 and the presence of multiple LC8 binding sites. Mice deficient in LC8 exhibit developmental defects [58, 92] and Drosophila with reduced LC8 levels die in early embryonic stages of development [93, 94]. Many LC8 binding partners contain multiple binding sites that must be fully removed in order to study the functional impact of LC8 binding in vivo , which becomes challenging when there is ambiguity in identifying all binding motifs.…”
Section: Lc8 Cross-linking Of Idp Duplex Scaffoldsmentioning
confidence: 99%
“…We previously unraveled the mechanism underlying the redox-dependent regulation of TNF-␣-induced NF-B activation, in which ROS oxidize LC8 to a homodimer linked by a reversible intermolecular disulfide bond, which promotes its dissociation from IB␣, allowing IB␣ to be phosphorylated and degraded and resulting in NF-B activation (20,21). Recently, we also showed that LC8 inhibits RANKL-induced osteoclastogenesis by regulating NF-B and protects against inflammation-induced or ovariectomy-induced bone loss in mice (31). Thus, it is likely that TRP14 attenuates OC differentiation by inhibiting NF-B through controlling the redox status of LC8.…”
Section: Discussionmentioning
confidence: 94%
“…Growing evidence suggests that RANKL induces transient production of reactive oxygen species (ROS) that mediate OC differentiation, and activation of NF-B and MAPKs is regulated by cellular redox change (26)(27)(28)(29)(30). We recently showed that LC8 inhibits RANKLinduced OC differentiation by suppressing NF-B and prevents inflammation-induced bone erosion (31). Thus, we sought to evaluate whether a novel cellular redox regulator, TRP14, regulates RANKL-induced activation of NF-B and MAPKs and subsequent osteoclast differentiation by using RAW 264.7 macrophage cells with ectopic expression of wild-type TRP14 and a catalytically inactive mutant, as well as its small interfering RNA.…”
mentioning
confidence: 99%